Revisiting the law and governance of trafficking, forced labor and modern slavery - Kotiswaran, Prabha (Cambridge : Cambridge University Press, 2017)
In the decades following the globalization of the world economy, trafficking, forced labor and modern slavery have emerged as significant global problems. States negotiated the Palermo Protocol in 2000 under which they agreed to criminalize trafficking, primarily understood as an issue of serious organized crime. Sixteen years later, leading academics, activists and policy makers from international organizations come together in this edited volume and adopt an inter-disciplinary, multi-stakeholder approach to revisit trafficking through the lens of labor migration and extreme exploitation and, in the process, rethink the law and governance of trafficking. This volume considers many key factors, including the evolving international law on trafficking, the relationship between trafficking, slavery, indenture and domestic migration law and policy as well as newly emergent techniques of governance, including indicators, all with a view to furthering prospects for lasting economic justice in a globalized world.
Machine generated contents note: Introduction. From sex panic to extreme exploitation: revisiting the law of'human trafficking' Prabha Kotiswaran; Part I. Revisiting the Text and Context of Article 3: 1. Trafficked and exploited: the urgent need for coherence in international law Michael Dottridge; 2. The international legal definition'trafficking in persons': scope and application Anne T. Gallagher; 3. Contemporary debt bondage,'self-exploitation' and the limits of the trafficking definition Janie A. Chuang; 4. Subjectivity of coercion: workers' experiences with trafficking in the United States Denise Brennan; Part II. Anti-Trafficking Law: A Legal Realist Critique: 5. The right to locomotion? Trafficking, slavery and the state Julia O'Connell Davidson; 6. Anti-trafficking and the new indenture Janet Halley; 7. Immigration controls and'modern-day slavery' Chantal Thomas; 8. Representing, counting, valuing: managing definitional uncertainty in the law of trafficking Kerry Rittich; Part III. Trafficking and New Forms of Governance: 9. Counting the uncountable: constructing trafficking through measurement Sally Engle Merry; 10. Addressing HIV/AIDS at the intersection of anti-trafficking and health law and policy Aziza Ahmed; 11. Brokered subjects and sexual investability Elizabeth Bernstein; Part IV. New Directions in Anti-Trafficking Law: The Rule of the ILO: 12. Raising the bar: the adoption of new ILO standards against forced labour Beate Andrees and Amanda Aikman; 13. Trafficking and forced labour: filling in the gaps with the adoption of the supplementary ILO standards, 2014 Lee Swepston; 14. Combating labor exploitation in the global economy: the need for a differentiated approach Robert Plant; 15. Human trafficking and forced labor: should companies be liable? Zuzanna Muskat-Gorska; Part V. Rethinking Trafficking through Migration Policy: 16. The paradox of'legality': temporary migrant worker programs and vulnerability to trafficking Hila Shamir; 17. The indentured mobility of migrant domestic workers: the case of Dubai Rhacel Salazar Parrenas and Rachel Silvey; 18. Migrants, unfree labour, and the legal construction of domestic servitude: migrant domestic workers in the UK Judy Fudge and Kendra Strauss.
Title from publisher's bibliographic system (viewed on 17 Jul 2017).
Keywords: Human trafficking -- Law and legislation; Forced labor -- Law and legislation; Slavery